Influence of Lactobacillus plantarum and cellulase on fermentation quality and microbial community in mixed silage of Solanum rostratum and alfalfa - Li, Yuyu; Wang, Hua; Zhang, Yandong; Ji, Yu; Guo, Lizhu; Hao, Lifen; Lin, Kejian (Frontiers in Microbiomes, 2025)
IntroductionIncreasing the research on the development and utilization of unconventional feed resources is one of the effective ways for the sustainable development of herbivorous animal husbandry. China is one of the countries most severely impacted by the invasion of the alien plant Solanum rostratum Dunal (S. rostratum), but this resource has not been used effectively.MethodsThe aim of this study was to investigate the effects of Lactobacillus plantarum and cellulase on the fermentation quality and microbial community in mixed silage of S. rostratum and alfalfa. Treatments were a control treatment with no additive (CK), Lactobacillus plantarum (LP), cellulase (CE), and Lactobacillus plantarum in combination with cellulase (L+C), all of which were stored at ambient temperature for 7, 15, 30, and 60 days.ResultsThe results showed that the mixture could retain dry matter (DM), crude protein (CP), and water soluble carbohydrates (WSC) content, increase lactic acid (LA) content, decrease pH and alkaloid content, and improve fermentation quality during silage. The use of additives increased the abundance of Lactobacillus and Weissella, which was related to the improvement of the quality of mixed silage and the degradation of total alkaloids. Differential microbial functions were mainly carbohydrate metabolism, biosynthesis of secondary metabolites and carbon metabolism.ConclusionThe application of additives and mixed silage provides a new idea for the feed utilization of S. rostratum.